A germline 1;3 translocation disrupting the VHL gene: a novel genetic cause for von Hippel-Lindau. Issue 1 (16th October 2020) - Ricketts, Christopher J; Vocke, Cathy D; Lang, Martin; Chen, Xiongfong; Zhao, Yongmei; Tran, Bao; Tandon, Mayank; Schmidt, Laura S; Ball, Mark W; Linehan, W Marston
Abstract : Von Hippel-Lindau (VHL) disease is an autosomal dominant hereditary tumour susceptibility disease caused by germline pathogenic variation of the VHL tumour suppressor gene. Affected individuals are at risk of developing multiple malignant and benign tumours in a number of organs. In this report, a male patient in his 20s who presented to the Urologic Oncology Branch at the National Cancer Institute with a clinical diagnosis of VHL was found to have multiple cerebellar haemangioblastomas, bilateral epididymal cysts, multiple pancreatic cysts, and multiple, bilateral renal tumours and cysts. The patient had no family history of VHL and was negative for germline VHL mutation by standard genetic testing. Further genetic analysis demonstrated a germline balanced translocation between chromosomes 1 and 3, t(1;3)(p36.3;p25) with a breakpoint on chromosome 3 within the second intron of the VHL gene. This created a pathogenic germline alteration in VHL by a novel mechanism that was not detectable by standard genetic testing. Karyotype analysis is not commonly performed in existing genetic screening protocols for patients with VHL. Based on this case, protocols should be updated to include karyotype analysis in patients who are clinically diagnosed with VHL but demonstrate no detectable mutation by existing genetic testing.